2020
DOI: 10.21307/eb-2020-003
|View full text |Cite
|
Sign up to set email alerts
|

Policy implications of the extent, nature and effects of young people’s exposure to alcohol promotion in sports-related contexts

Abstract: Sports-related alcohol promotion is a primary mechanism via which young people are exposed to alcohol advertising. Efforts to reduce this exposure need to be informed by information relating to: 1) the prevalence of sports-related alcohol promotion in live, broadcast and online contexts; 2) the nature of this promotion; 3) the effects on young people of exposure to these forms of alcohol promotion; and 4) evidence-based strategies that have been demonstrated to address alcohol promotion activities that connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…22 In Australian sports and, in particular, the most popular spectator sports such as Australian rules football, rugby league and cricket, alcohol marketing is commonplace. [23][24][25][26][27][28] Estimates of sport-related alcohol industry marketing expenditure in Australia vary between A$50 million and A$300 million. 29 Exposure to alcohol marketing during sports broadcasts can be particularly problematic for children aged 8-12 years, who tend to become fascinated with real-life heroes, such as sport stars.…”
Section: Potential Financial Impact On Television Network Of a Ban On...mentioning
confidence: 99%
See 1 more Smart Citation
“…22 In Australian sports and, in particular, the most popular spectator sports such as Australian rules football, rugby league and cricket, alcohol marketing is commonplace. [23][24][25][26][27][28] Estimates of sport-related alcohol industry marketing expenditure in Australia vary between A$50 million and A$300 million. 29 Exposure to alcohol marketing during sports broadcasts can be particularly problematic for children aged 8-12 years, who tend to become fascinated with real-life heroes, such as sport stars.…”
Section: Potential Financial Impact On Television Network Of a Ban On...mentioning
confidence: 99%
“…Alignment with a healthy activity, such as sport, is highly beneficial for alcohol brands as the association can obscure the health risks related to their products 22 . In Australian sports and, in particular, the most popular spectator sports such as Australian rules football, rugby league and cricket, alcohol marketing is commonplace 23–28 . Estimates of sport‐related alcohol industry marketing expenditure in Australia vary between A$50 million and A$300 million 29…”
mentioning
confidence: 99%
“…In Australia, many of the national sporting organisations, competitions, events and teams have sponsorship arrangements with alcohol brands, particularly in popular sports such as Australian rules football (AFL), rugby league (NRL) and cricket, which account for approximately two-thirds of all alcohol sponsorships [ 2 ]. Elite sport sponsorship achieves high reach and strong engagement through live spectatorship as well as those watching on television or other screens [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The focus on alcohol advertising in the present study was chosen for several reasons. First, a substantial body of research evidence is available to inform deliberations about alcohol advertising policy (for recent reviews see [22][23][24][25][26]). The evidence base has developed to a level where it can be concluded that exposure to alcohol advertising is a cause of alcohol use among young people [27,28].…”
Section: Introductionmentioning
confidence: 99%